Aortic shape with high-acute isthmic angle post frozen elephant trunk reconstruction is associated with worse postoperative outcomes: Multisite, principal component analysis, retrospective study - Schäfer, Michal; Glotzbach, Jason P.; Pereira, Sara J.; Sharma, Vikas; Goodwin, Matthew L.; Cleveland, Joseph C.; Selzman, Craig H.; Carroll, Adam; Barker, Alex J.; Aftab, Muhammad; Reece, T. Brett (JTCVS Structural and Endovascular, 2024)
Aortic shape and geometry after surgical reconstruction have been shown to be important determinants of flow hemodynamics, aortic remodeling, and clinical outcomes. In this study, we investigated aortic shapes post-frozen elephant trunk (FET) reconstruction using statistical shape modeling by principal component analysis and correlated discovered shape variations with the postoperative outcomes. Patients from 3 institutions who underwent computed tomography (CT) angiography post-FET aortic reconstruction for type A dissection or ascending thoracic aortic aneurysms were included. A 3-dimensional aortic model was generated from CT angiography, and the aortic centerline was calculated for each subject. Principal components describing aortic shape variations were then correlated with the cumulative rate of postoperative aortic events requiring intervention. A total of 135 subjects across 2 sites with postoperative CT and surveillance data were included in the study. Identified first principal component accounting for 31.6% of geometric shape variation in the entire cohort described angle variability at the region of the aortic isthmus. On the basis of the degree of isthmic angulation quantitatively defined by the principal component score, we separated the cohort into high and low isthmic angle groups. Patients with high isthmic angle had greater 5-year freedom from aortic events with 49.5% compared with 78.6% in the low isthmic angle group (P = .024). Aortic shape variation defined by the acute angle of the aortic isthmus has been associated with aortic events and lower freedom from intervention post-FET operation. These results add to the increasing amount of evidence implicating acute isthmic angle from overt downstream aortic remodeling postcomplex aortic repair. Further biomechanical studies are required to identify the mechanistic link between isthmic geometry and patient-specific aortic remodeling.